YEAST POPULATION OF SACCHAROMYCES CEREVISIAE IN THE FECES OF YOUNG AND ADULT ETAWA CROSSBREED GOATS IN SUKAWATI DISTRICT, GIANYAR REGENCY - Levina, Stephanie; I Nengah Kerta Besung; I Gusti Ketut Suarjana (Buletin Veteriner Udayana, 2024)
Sacharomyces cerevisiae is a yeast that has great potential to increase the nutritional value of feed ingredients and increase the activity of rumen microbial performance, by utilizing oxygen so that rumen conditions are anaerobic, which makes cellulolytic bacteria develop well. This study aims to determine the population of S. cerevisiae yeast in young and adult etawa crossbreed goat feces. The samples used were 27 of etawa crossbreed goat feces from etawa crossbreed goat farms in Sukawati Sub-District, Gianyar Regency. There are three treatments given, namely etawa crossbreed goat feces from young goats aged 0-2 months, 3-5 months and adult goats aged over 6 months. This study used a Randomized Group Design by comparing the yeast population of S. cerevisiae in the feces of young and adult etawa crossbreed goats, which was done microscopically using a hemocytometer. The results showed that the average yeast content of S. cerevisiae in the feces of young etawa crossbreed goats aged 0-2 months was 25.56 x 104 ± 16,666.667 cells/ml, 3-5 months 42.22 x 104 ± 26,352.314 cells/ml, and adult goats aged 6 months to above 94.44 x 104 ± 30,459.445 cells/ml. There is a very significant difference, the burden of the yeast S. cerevisiae in the feces of adult Etawa crossbreed goats is higher compared to young goats. Further testing needs to be done on the type of yeast found in the feces and stomach of Etawa crossbreed goats.